Regulating Local Government Financing Vehicles and Public-Private Partnerships in China - Jin, Hui (IMF Working Papers; Working Paper ;, 2016)
In this paper, we argue that there is much room for China to strengthen its regulatory framework for public-private partnerships (PPPs). We show that infrastructure projects carried out through local government financing vehicles (LGFVs) were largely unregulated PPPs, and significant fiscal risks have already manifested themselves. While PPPs can potentially provide efficiency gains, they can also be used by governments to circumvent budgetary borrowing constraints. Therefore, effective PPP regulation is key to delivering PPPs' benefits while containing their potential fiscal risks. The authorities have taken concrete steps in order to establish a sound regulatory framework and foster a new generation of PPPs. However, to make the framework effective, we highlight a few issues to be resolved. Based on international best practice, we propose a four-pillar regulatory framework for China, which could be implemented gradually in three stages.